2023
DOI: 10.3390/molecules28104084
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Acids Rescue Iron-Induced Damage in Murine Pancreatic Cells and Tissues

Abstract: Iron is an essential element involved in a variety of physiological functions. However, excess iron catalyzes the generation of reactive oxygen species (ROS) via the Fenton reaction. Oxidative stress, caused by an increase in intracellular ROS production, can be a contributory factor to metabolic syndromes such as dyslipidemia, hypertension, and type 2 diabetes (T2D). Accordingly, interest has grown recently in the role and use of natural antioxidants to prevent iron-induced oxidative damage. This study invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A summary of polyphenols as biomarkers of oxidative stress in diabetes[152,161,[235][236][237][238][239][240].…”
mentioning
confidence: 99%
“…A summary of polyphenols as biomarkers of oxidative stress in diabetes[152,161,[235][236][237][238][239][240].…”
mentioning
confidence: 99%
“…119 In a mouse model with tumor-induced liver injury, a dietary As a result, the levels of its downstream antioxidant genes, such as HO-1, NQO1, GCLC, and GPx4, increased in the pancreas. 121 In the same year, Ni et al reported that resveratrol (200 mg/kg) promoted the recovery of motor function in spinal cord injured (SCI) mice by inhibiting lipid peroxides production and iron accumulation through activation of the Nrf2/GPx4 pathway. 122 Deng et al found that quercetin (40 mg/kg) upregulated the expression of antioxidant enzymes such as Sirt1, Nrf2, GPx4, SOD, and GSH in a mouse model of lipopolysaccharide-induced acute lung injury, which in turn mitigated the lung injury.…”
Section: Fpps Classification and Antioxidant Propertiesmentioning
confidence: 99%
“…Treatment of mice with FA or FAS (20 μmol/L) increased the level of nuclear translocation of the Nrf2 gene in the pancreas. As a result, the levels of its downstream antioxidant genes, such as HO-1, NQO1, GCLC, and GPx4, increased in the pancreas . In the same year, Ni et al reported that resveratrol (200 mg/kg) promoted the recovery of motor function in spinal cord injured (SCI) mice by inhibiting lipid peroxides production and iron accumulation through activation of the Nrf2/GPx4 pathway .…”
Section: Fpps Classification and Antioxidant Propertiesmentioning
confidence: 99%